2021
DOI: 10.1111/his.14395
|View full text |Cite
|
Sign up to set email alerts
|

Verrucous carcinoma of the oesophagus is a genetically distinct subtype of oesophageal squamous cell carcinoma

Abstract: Verrucous carcinoma of the oesophagus is a genetically distinct subtype of oesophageal squamous cell carcinoma Aims: Oesophageal verrucous carcinoma (VSCC) is a rare and morphologically distinct type of oesophageal squamous cell carcinoma (SCC). Diagnosing VSCC on biopsy material is challenging, given the lack of significant atypia and the presence of keratinising epithelium and exophytic growth. The molecular pathogenesis of VSCC remains unclear. The aim of this study was to characterise the genomic landscape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Isidro et al reported the first molecular study on VC. 33 Unlike conventional ESC, TP53 mutations were much less likely to be detected in VC. Copy number variants for CDKN2A, CDKN2B, and CCND1 were significantly less frequent in VC than in conventional ESC.…”
Section: Verrucous Squamous Cell Carcinomamentioning
confidence: 94%
See 3 more Smart Citations
“…Isidro et al reported the first molecular study on VC. 33 Unlike conventional ESC, TP53 mutations were much less likely to be detected in VC. Copy number variants for CDKN2A, CDKN2B, and CCND1 were significantly less frequent in VC than in conventional ESC.…”
Section: Verrucous Squamous Cell Carcinomamentioning
confidence: 94%
“…A non-invasive component of verrucous carcinoma adjacent to invasive verrucous carci- noma depicted in one paper demonstrated exophytic growth with verruciform architecture, preserved epithelial maturation, abrupt keratinization, and lack of nuclear overlapping or atypia. 33 Sequencing of the non-invasive squamous component showed nearly identical mutations in SMARCA4, FBXW7, and NOTCH1 (Table 1) compared to the invasive squamous component. 33 Cases 2 and 3 in this series showed the morphology of carcinoma cuniculatum in the deep portion of the lesion with keratin-filled cysts.…”
Section: Verrucous Squamous Cell Carcinomamentioning
confidence: 98%
See 2 more Smart Citations
“…Verrucous carcinoma may be found in the entire mucosa of the upper aerodigestive tract, including oral cavity, pharynx, cervical esophagus, and nasal cavities [30,31 ▪ ]. In the larynx, the most common subsites of LVC are the glottis and supraglottis (Table 1) [8–10,12–17,24,32–38].…”
Section: Clinical and Pathological Featuresmentioning
confidence: 99%